2017
DOI: 10.1091/mbc.e16-12-0865
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of TGFβ in lens epithelial cell fate: implications for secondary cataract

Abstract: TGFβ signaling is linked to posterior capsule opacification (PCO), the most common complication of cataract surgery. TGFβ can induce primary lens epithelial cells to differentiate into two disparate, PCO-causing abnormal cell phenotypes, a variation of the TGFβ paradox. Analysis of the signaling pathways downstream of TGFβ reveals novel therapeutic targets for PCO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 112 publications
3
63
0
Order By: Relevance
“…Future studies will be needed to address the following questions: a) Do β/γ-crystallin regulatory regions contain AP-1 and Ets binding sites? [189]; b) BMP signaling is known to regulate the expression of αA-crystallin gene [190, 191] and maybe other crystallins. Are crystallin genes regulated by Smad proteins?…”
Section: Lens Morphogenesis and Gene Regulatory Networkmentioning
confidence: 99%
“…Future studies will be needed to address the following questions: a) Do β/γ-crystallin regulatory regions contain AP-1 and Ets binding sites? [189]; b) BMP signaling is known to regulate the expression of αA-crystallin gene [190, 191] and maybe other crystallins. Are crystallin genes regulated by Smad proteins?…”
Section: Lens Morphogenesis and Gene Regulatory Networkmentioning
confidence: 99%
“…It is known that TGFβ signaling is increased during cataract surgery, presumably as part of the wound-healing response (Sponer et al, 2005;Saika et al, 2002). It has long been proposed, and experimentally supported in primary culture systems, that TGFβ signaling contributes to myofibroblast differentiation in PCO, as it does in many fibrotic conditions in other organs (Meacock et al, 2000;Wormstone et al, 2002Wormstone et al, , 2006Wormstone et al, , 2009Saika, 2004;de Iongh et al, 2005;Vasavada and Praveen, 2014;Nibourg et al, 2015;Boswell et al, 2017). We have recently shown that TGFβ induces some epithelial cells in primary embryonic chick lens cultures (DCDMLs) to differentiate into myofibroblasts, and other cells in the same wells to form immature lens fiber cells.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that TGFβ induces some epithelial cells in primary embryonic chick lens cultures (DCDMLs) to differentiate into myofibroblasts, and other cells in the same wells to form immature lens fiber cells. The latter process is distinct from induction of fiber differentiation by FGF in that it does not require BMP signaling and is only partially reduced by fibroblast growth factor receptor (FGFR) inhibition (Boswell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many lens models have been developed to study PCO (Liu et al, ; West‐Mays et al, ; Wormstone and Eldred, ; Boswell et al, ). The classic model is the human capsular bag cultures, which have been used to study wound repair and fibrosis (Liu et al, ).…”
Section: Lessons Learned From the Study Of The Lensmentioning
confidence: 99%
“…Thus, an imbalance in TGFβ signaling can lead to fibrotic disease progression. In the lens, TGFβ signaling has been linked to the development of PCO (Wormstone et al, ; Wormstone et al, ; West‐Mays et al, ; Eldred et al, ; Boswell et al, ). The latent form of TGFβ is bound within the extracellular matrix and its activation involves integrin receptors, particularly αvβ6.…”
Section: Lessons Learned From the Study Of The Lensmentioning
confidence: 99%